Pelajar Pancasila Hebat: Meningkatkan Efektivitas Pembelajaran melalui Program P5 Bangunlah Jiwa Raganya - Prabandari, Anandhiya Intan; Komalasari, Febyana Putri; Maisaraah, Sausan Nuhaa (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
The "Strengthening the Profile of Pancasila Students" (P5) program is designed to enhance students' manners, learning effectiveness, and physical and mental health at SMK Widya Manggala Purbalingga through interactive training, workshops, and systematic counseling. This community service program was implemented at SMK Widya Manggala Purbalingga from November 4–8, 2024, with a focus on student health. The implementation method consists of three main stages: preparation, execution, and evaluation. The evaluation results indicate an increase in the students' average score from 65 before the program to 80 after the program. The program's implementation successfully improved students' awareness of manners, as they demonstrated more polite and ethical behavior; effective learning skills, by developing time management abilities and independent study strategies; and health knowledge, increasing their awareness of the importance of maintaining physical and mental well-being. This program has proven effective in shaping students' character based on Pancasila values and enhancing their well-being holistically. It provides a tangible contribution to preparing a generation of excellent, strong-charactered individuals who can actively contribute to society.